Perception Analysis of Consumers' Purchase Intentions for Jatropha Aromatherapy Candles - Putri, Dessy Iriani; Sadiah, Anisa Halimatu; Nauly, Dahlia (Universitas Muhammadiyah Jakarta, 2024)
Perceived price, perceived value, and perceived quality are crucial in shaping the purchase intention of Jatropha aromatherapy candles. This study analyzes the characteristics of Jatropha aromatherapy candle consumers and the effect of perceived price, perceived value, and perceived quality on the purchase intention of Jatropha aromatherapy candles. The data analysis technique used in this research is a quantitative analysis using SEM PLS. The results of this study indicate that Jatropha customers are mostly female, with the highest age range of 15–25 years. Most occupations are college students, and most are domiciled in DKI Jakarta. Perceived quality positively and significantly affects the purchase intention of Jatropha aromatherapy candles. Meanwhile, perceived price and value do not affect the purchase intention of Jatropha aromatherapy candles.